The positive effect on ketamine as a priming adjuvant in antidepressant treatment. - Melo, A.; Kokras, N; Dalla, C; Ferreira, C; Ventura-Silva, A P; Sousa, N.; Pêgo, J M (Transl Psychiatry, 2015)
Ketamine is an anesthetic with antidepressant properties. The rapid and lasting effect of ketamine observed in preclinical and clinical research makes it a promising therapeutic to improve current major depression (MD) treatment. Our work intended to evaluate whether the combined use of classic antidepressants (imipramine or fluoxetine) and ketamine would improve the antidepressant response. Using an animal model of depressive-like behavior, we show that the addition of ketamine to antidepressants anticipates the behavioral response and accelerates the neuroplastic events when compared with the use of antidepressants alone. In conclusion, our results suggest the need for a reappraisal of the current pharmacological treatment of MD.
Keywords: Animals; Antidepressive Agents; anxiety; aspartic acid; Behavior, Animal; Brain; Depression; Depressive Disorder, Major; Disease Models, Animal; Drug Therapy, Combination; Fluoxetine; glutamic acid; Imipramine; Ketamine; Male; Prefrontal Cortex; Pyramidal Cells; Rats; Rats, Wistar; Stress, Psychological